Adherence to Mediterranean Diet Is Associated With Better Glycemic Control in Children With Type 1 Diabetes: A Cross-Sectional Study - Dominguez-Riscart, Jesus; Buero-Fernandez, Nuria; Garcia-Zarzuela, Ana; Morales-Perez, Celia; Garcia-Ojanguren, Ana; Lechuga-Sancho, Alfonso M. (Frontiers in Nutrition, 2022)
Type 1 diabetes (T1D) is a chronic condition, with increased morbidity and mortality, due to higher rate of cardiovascular disease among other factors. Cardiovascular risk increases with worse glycemic profile. Nutrition has a deep impact on diabetes control. Adherence to the Mediterranean diet (MD) has been shown to decrease cardiovascular risk in children and adults with obesity and in adults with type 2 diabetes, but its impact in T1D children has been scarcely analyzed. We hypothesized that the degree of adherence to MD could relate to increased time in range in children with T1D. Patients and Methods: Cross-sectional analysis involving two university hospitals. We measured the adherence to MD with the KIDMED questionnaire, a validated tool for this purpose. A score of <5 indicates poor adherence to MD, while a good adherence is indicated by a score >7. Demographic and clinical, data were registered on the same day the questionnaire was taken, with informed consent. Additionally, patient’s ambulatory glucose profiles (AGPs), were registered from the participants’ glucose monitors (continuous or flash devices), daily insulin needs were recorded from patients’ insulin pumps (n=28). Other cardiovascular risk factors such as lipid profile, and vitamin D levels and other biochemical parameters were registered from a blood test, performed two weeks before recruitment, as part of the patients’ annual screening. Results: 97 patients (44 girls) with an average age of 11.4 years (±3.01) were included. 71 of them were on multiple daily injection regimens, and all had either continuous or flash glucose monitoring. 53 had HbA1c levels of <7.5%, while only 21 had a TIR >70% Contingency analysis showed that the odds of having HbA1c <7.5%, increase in children with KIDMED score >7 (O.R. 2,38; ICR 1.05 – 5.41; p = 0.036). Moreover, KIDMED score and HbA1c levels were negatively correlated (R: -0.245; p-value: 0.001), while KIDMED score and TIR showed a positive correlation (R: 0.200; p-value: 0.009). Conclusions: Our data suggest that adherence to MD may contribute to a better glycemic control in children. This should be taken into account at the time of nutritional education on T1D patients and their families.